Community health workers at the dawn of a new era: 1. Introduction: tensions confronting large-scale CHW programmes - Stephen Hodgins; Maryse Kok; David Musoke; Simon Lewin; Lauren Crigler; Karen LeBan; Henry B. Perry (BMC, 2021)
Abstract Background Community health worker (CHW) programmes are again receiving more attention in global health, as reflected in important recent WHO guidance. However, there is a risk that current CHW programme efforts may result in disappointing performance if those promoting and delivering them fail to learn from past efforts. This is the first of a series of 11 articles for a supplement entitled "Community Health Workers at the Dawn of a New Era". Methods Drawing on lessons from case studies of large well-established CHW programmes, published literature, and the authors' experience, the paper highlights major issues that need to be acknowledged to design and deliver effective CHW programmes at large scale. The paper also serves as an introduction to a set of articles addressing these issues in detail. Results The article highlights the diversity and complexity of CHW programmes, and offers insights to programme planners, policymakers, donors, and others to inform development of more effective programmes. The article proposes that be understood as actors within community health system(s) and examines five tensions confronting large-scale CHW programmes; the first two tensions concern the role of the CHW, and the remaining three, broader strategic issues: 1) What kind of an actor is the CHW? A lackey or a liberator? Provider of clinical services or health promoter? 2) Lay versus professional? 3) Government programme at scale or nongovernmental organization-led demonstration project? 4) Standardized versus tailored to context? 5) Vertical versus horizontal? Conclusion CHWs can play a vital role in primary healthcare, but multiple conditions need to be met for them to reach their full potential.